2009
DOI: 10.1590/s1808-86942009000500004
|View full text |Cite
|
Sign up to set email alerts
|

Report on hearing loss in oncology

Abstract: Ci splatin is used frequently as an antineoplastic drug in the treatment of many different cancers. However, when used in doses over 360mg/m 2 , ototoxicity may ensue, resulting in loss of hearing. Criteria for identifying and quantifying hearing loss have been devised. Aim: To describe the features of different hearing loss classification systems and to identify their implications and use in oncologic patients. Method: Hearing loss was classified in 31 patients before and after chemotherapy, according to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…Therefore, the Health Professions Council of South Africa (HPCSA) [34] recommends the sequential use of ASHA [22] criteria and then the NCI-CTCAE grading scale [30] to grade the severity of the ototoxic change which relates to the functional impact on the patient's quality of life. The percentage of significant ototoxic change in the current study, being higher than previously reported in South Africa [35], and other international studies [36][37][38][39][40][41][42], may be attributed to the use of extended high-frequency audiometry in the current study. However, there is still a higher percentage of ototoxic change in the current study compared to other studies that also utilized extended high-frequency audiometry [9,40], which could be due to differences in the study population, such as the high incidence of HIV and the use of ARTs.…”
Section: Discussioncontrasting
confidence: 73%
“…Therefore, the Health Professions Council of South Africa (HPCSA) [34] recommends the sequential use of ASHA [22] criteria and then the NCI-CTCAE grading scale [30] to grade the severity of the ototoxic change which relates to the functional impact on the patient's quality of life. The percentage of significant ototoxic change in the current study, being higher than previously reported in South Africa [35], and other international studies [36][37][38][39][40][41][42], may be attributed to the use of extended high-frequency audiometry in the current study. However, there is still a higher percentage of ototoxic change in the current study compared to other studies that also utilized extended high-frequency audiometry [9,40], which could be due to differences in the study population, such as the high incidence of HIV and the use of ARTs.…”
Section: Discussioncontrasting
confidence: 73%
“…Importantly, in our experience, the average age of Veterans entering treatment is 60 yr and most report a history of significant noise exposure [4][5], which accounts for the high rate of preexisting hearing loss in this population. It is well documented that hearing loss adversely impacts quality of life [6]; psychosocial functioning [7]; and one's ability to obtain, process, and understand basic health information [8]; therefore, it is an undeniably important side effect to monitor during chemotherapy. Furthermore, health-related quality of life concerns are important to oncologists because improved treatments and early diagnoses have increased long-term cancer survivability.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies with a prospective enrollment of cancer patients following strict audiological workup protocols corroborate this hypothesis. Those studies reported a much higher ototoxicity occurrence, reaching up to 64%, depending on the hearing loss criteria (Helson et al, 1978;Aguilar-Markulis et al, 1981;Reddel et al, 1982;Schultz et al, 2009). Furthermore, centers performing additional extended high-frequency audiometry (up to 20 kHz) reported a higher occurrence of cisplatin ototoxicity than centers with the standard audiometric testing (up to 8 kHz), as used in the present study (Zuur et al, 2008;Arora et al, 2009).…”
Section: Limitations and Strengthsmentioning
confidence: 50%